Effect of Bacterial Flora on Postimmunization Gastritis following Oral Vaccination of Mice with Helicobacter pylori Heat Shock Protein 60 - Yamaguchi, Hiroyuki (American Society for Microbiology, 2003)
In order to assess the efficacy of oral Helicobacter pylori heat shock protein 60 (HSP60) as a vaccine, protection against H. pylori infection in specific-pathogen-free (SPF) C57BL/6 and germfree (GF) IQI mice was examined. Prophylactic oral vaccination of these two strains of mice with either H. pylori HSP60 or Escherichia coli GroEL inhibited H. pylori colonization by 90 to 95% at 3 weeks postinfection (p.i.). However, these mice were only partially protected because bacterial loads increased in all animals at 10 weeks p.i. Anti-H. pylori HSP60 immunoglobulin G was detected in serum at 3 weeks p.i. in mice vaccinated with either H. pylori HSP60 or GroEL. Significant increases in the gastritis scores were observed only in SPF mice immunized with H. pylori HSP60. These results indicate that oral vaccination with H. pylori HSP60 has partial protective effects on subsequent H. pylori infection but also induces postimmunization gastritis. However, GF mice immunized with H. pylori HSP60 did not suffer from severe gastritis. Therefore, the presence of bacterial flora appears to contribute to the induction of postimmunization gastritis.